Clinical, humanistic, and economic burden of osteoarthritis among noninstitutionalized adults in the United States. Issue 11 (November 2019) - Zhao, X.; Shah, D.; Gandhi, K.; Wei, W.; Dwibedi, N.; Webster, L.; Sambamoorthi, U.
Summary: Objective: To estimate the burden of osteoarthritis (OA) among noninstitutionalized adults (≥18 years of age) in the US. Design: Weighted nationally representative data from the 2015 Medical Expenditure Panel Survey were used to estimate OA prevalence in noninstitutionalized adults and compare adults with OA to those without OA for clinical (pain interference with activities [PIA], functional limitations), humanistic (health-related quality-of-life [HRQoL]) and economic outcomes (healthcare costs, wage loss). Productivity/wage loss was estimated among employed working-age adults (18–64 years). Multivariable regression analyses examined the associations between OA and outcomes. Results: In 2015, 10.5% (25.6 million) of noninstitutionalized US adults reported having any OA. Regression analyses indicated that adults with OA were significantly more likely than those without OA to report moderate (adjusted odds ratios [AOR] 1.99; 95% confidence interval [CI] 1.65–2.40] or severe PIA (AOR 2.59; 95% CI 2.21–3.04), any functional limitation (AOR 2.51; 95% CI 2.21–2.85), and poorer HRQoL on the SF-12 version 2 Physical Component Summary score (adjusted beta [standard error] −3.88 [0.357]; P < 0.001). Adjusted incremental annual total healthcare costs and lost wages among adults with OA relative to those without OA were 1778 and 189 per person, respectively, resulting in estimated national excess costs of 45 billion and 1.7 billion, respectively. Conclusions: OA affects approximately 10% of noninstitutionalized adults in the US, resulting in substantial clinical, humanistic, and economic burdens.